Cell signalling in CNS and immune system in depression and during antidepressant treatment: focus on glial and natural killer cells - Kovářů, Hana; Páv, Marek; Kovářů, František; Raboch, Jiří; Fišerová, Anna (Neuro-endocrinology letters, 2009)
CNS, endocrine and immune systems share the same molecules: neurotransmitters, cytokines and hormones to communicate within and among each other. Depression is associated with abnormalities in the noradrenergic, serotonergic and dopaminergic neurotransmitter systems and reductions in the level of their precursors and metabolic turnover. Most of these signalling molecules use trimeric G-proteins as a transduction system to transfer extracellular signal into cellular response. Altered levels or function of signalling proteins, especially alpha subunits of trimeric G-proteins, were found in post-mortem brain tissue and leukocytes of subject suffering from major depression. There is a considerable evidence that inflammatory response and immune system changes are the part of depression. Components of cellular immune system natural killer cells, important effectors of immune surveillance, are sensitive to stress response, and their functions are compromised in depressive subjects. Many lines of evidence also point to the loss of both neuronal and glial plasticity and neurotrophic factor support under chronic stress or in depression. There is an increasing knowledge of the role of astrocytic cells in neuroplastic processes and neurotransmitter metabolism. Alterations in the glial populations are observed in major depressive subjects. Antidepressant treatment is modulating glial signalization cascades, increasing production of neurotrophic molecules, supporting neuroplasticity processes, and also modulating functions of natural killers. At the level of membrane signalling, antidepressants show a direct influence upon G alpha subunit levels in both immune system and CNS. These findings support the view that antidepressants influence activity of natural killer and astrocytic populations, and this could be of importance in the depression etiopathogenesis and/or treatment.
Keywords: centrální nervový systém; neuroglie; antidepresiva; signální transdukce; Neuroglia; Animals; Central Nervous System; lidé; Killer Cells, Natural; Antidepressive Agents; Depressive Disorder; Humans; zvířata; buňky NK; depresivní poruchy; Signal Transduction